Introduction to framing - Shopware (Firm) (New Jersey : Shopware Productions, 2004)
This program will detail the basics of many framing applications, including layout terms and principles, construction techniques, and standard framing plans
Title from title screen
Teacher's guide online on www.shopware.usa.com
DVD format
Keywords: House construction; House framing; Wooden-frame houses -- Design and construction; Building trades